Changes in global strain of puborectalis muscle during pregnancy and postpartum. - van de Waarsenburg, M. K.; Withagen, M. I. J.; Schweitzer, K. J.; van der Vaart, C. H.; Grob, A. T. M.; Hitschrich, N. (Ultrasound in Obstetrics & Gynecology, 2018)
Objective: One of the functional parameters that can be assessed by ultrasound is muscle strain, which represents the extent of deformation of the muscle from its original shape when forces are applied to the tissue under study. The aim of this study was to evaluate the effect of pregnancy and delivery on the puborectalis muscle, by assessing changes in global strain of the muscle during and after pregnancy.Methods: This was a secondary analysis of a prospective observational study on the association between stress urinary incontinence and levator ani muscle avulsion after delivery. Two-hundred and eighty nulliparous pregnant women underwent four-dimensional transperineal ultrasound assessments at 12 and 36  weeks of gestation, and 6 months postpartum. Tomographic ultrasound images were constructed and the puborectalis muscle was delineated by hand using programming software. After delineation, the length of the midline of the puborectalis muscle was measured at rest and during maximum pelvic floor muscle contraction, and global strain was expressed as percentile difference. Postpartum results were analyzed separately for vaginal, operative (vacuum) vaginal and Cesarean delivery. Differences in global strain of the puborectalis muscle according to mode of delivery were compared using a paired-sample t-test. The effect of partial or complete avulsion of the puborectalis muscle on postpartum strain was evaluated by ANOVA.Results: In total, 254 datasets were analyzed. Global strain of the puborectalis muscle did not change during pregnancy, but after spontaneous or operative vaginal delivery the global strain diminished significantly. No significant change was observed in strain of the puborectalis muscle after Cesarean delivery. Women who suffered complete bilateral avulsion had significantly lower strain compared with women with an intact puborectalis muscle.Conclusion: Spontaneous or operative vacuum vaginal birth and complete bilateral avulsion of the puborectalis muscle influence negatively the strain of the puborectalis muscle. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.